Estimation of scrub typhus incidence and spatiotemporal multicomponent characteristics from 2016 to 2023 in Zhejiang Province, China - Wu, Haocheng; Xue, Ming; Wu, Chen; Lu, Qinbao; Ding, Zheyuan; Wang, Xinyi; Fu, Tianyin; Yang, Ke; Lin, Junfen (Frontiers in Public Health, 2024)
China is one of the main epidemic areas of scrub typhus, and Zhejiang Province, which is located in the coastal area of southeastern China, wasis also considered as a key region of scrub typhus. However, there may be significant reporting bias in the number of reported cases of scrub typhus, to the extent that its epidemiological patterns cannot beare not clearly understood. The purpose of this study iswas to estimate the possible incidence of scrub typhus and to identify the main driving components affecting the occurrence of scrub typhus at the county level.The kriging interpolation method was used to estimate the possible incidence of scrub typhus. Additionally, a multivariate time series model was applied to identify the main driving components affecting the occurrence of scrub typhus in different regions.The estimated area with case occurrence is was relatively wider. There are were 41 counties in Zhejiang Province with thean annual reported case count of less than 1, while from the estimated annual incidence, the number of counties with less than 1 case has decreased to 21. The average annual number of cases in most regions fluctuates fluctuated between 0-and 15. The number numbers of cases in the central urban area of Hangzhou Citycity, Jiaxin Citycity and Huzhou City city does did not exceed 5. The estimated incidence level was higher than the current reported number of cases, and the possible impact area of the epidemic is was also wider than the areas with reported cases. The main driving factors of the scrub typhus epidemic in Zhejiang are included endemic components such as natural factors, but there is was significant heterogeneity in the composition of driving factors in different regions. Some regions are were driven by spatiotemporal spread across regions, and the time autoregressive effect in individual regions cannot could not be ignored. It suggestsThese results that monitoring of cases, vectors, and pathogens of scrub typhus should be strengthened. Furthermore, each region should take targeted prevention and control measures based on the main driving factors of the local epidemic to improve the accuracy of prevention and control.